Progresi Weight Faltering Menjadi Severely Underweight akibat Pola Makan Maladaptif: Case Report - Aty Firsiyanti; Gina Noor Djalilah; Yusian Eri Fitria; Mufidah Hariani; Salsabila Rayhani; Farida Kholifah; Adristy Anneira Vanka Meisya; Nabilah Isyraq Syahirah; Zetty Fortune Ananta Mulia (PROCEEDING UMSURABAYA, 2026)
Background: Weight faltering in early childhood may develop gradually and be difficult to recognize early. It is not always caused by organic disease, but may reflect an imbalance between nutritional needs and intake, especially during the complementary feeding period. Case presentation: A 2-year-30-day-old girl was brought by her mother because of no significant weight gain since 7 months of age. She was exclusively breastfed for 6 months and started complementary feeding at 6 months. Since then, she had poor appetite, was difficult to feed, and consumed only 3 small spoonfuls @5 grams/spoon per meal. At 7 months, her mother noticed poor weight gain, but no specific growth monitoring was provided until around 1 year of age. The child was cared for daily by her grandmother while her mother worked as a teacher. Complementary foods were usually prepared by the mother before work and often consisted of vegetables and fruits, while animal and plant protein were rarely given. After 1 year of age, her intake became by UHT milk and formula. She also frequently consumed snack foods and tea. High-calorie milk was poorly accepted, and vitamin sprinkle supplementation reportedly reduced her appetite. At presentation, her weight was 8.5 kg and height was 78 cm. WHO growth chart interpretation showed underweight, stunted, and normal weight-for-height. No significant prenatal, perinatal, developmental, past medical, or family history directly explained the growth problem. Conclusion: This case illustrates chronic weight faltering beginning during complementary feeding, most likely related to prolonged inadequate intake and maladaptive feeding patterns. Early anthropometric monitoring, exclusion of organic causes, and caregiver-based feeding intervention are essential to support catch-up growth.